The Roles of circRNAs in Intervertebral Disc Degeneration: Inflammation, Extracellular Matrix Metabolism, and Apoptosis - Hao Li; Lijun Tian; Jianhua Li; Yongjin Li; Lilong Du; Zhenxin Huo; Baoshan Xu (Analytical Cellular Pathology)
Low back pain (LBP) is seriously harmful to human health and produces heavy economic burden. And most scholars hold that intervertebral disc degeneration (IDD) is the primary cause of LBP. With the study of IDD, aberrant expression of gene has become an important pathogenic factor of IDD. Circular RNAs (circRNAs), as a kind of noncoding RNA (ncRNA), participate in the regulation of genetic transcription and translation and further affect the expression of inflammatory cytokine, metabolism of extracellular matrix (ECM), the proliferation and apoptosis of cells, etc. Therefore, maybe it will become a new therapeutic target for IDD. At present, our understanding of the mechanism of circRNAs in IDD is limited. The purpose of this review is to summarize the mechanism and related signaling pathways of circRNAs in IDD reported in the past. Particularly, the roles of circRNAs in inflammation, ECM metabolism, and apoptosis are emphasized.